Peningkatan Hardskill Ibu Rumah Tangga Sebagai Upaya Meningkatkan Penghasilan Keluarga Melalui Pelatihan Pembuatan Telur Asin Di Desa Bajo Kecamatan Soromandi - Wandira, Ica Ayu; Yanuarianto, Oscar; Dahlanuddin, Dahlanuddin (Jurnal Gema Ngabdi, 2024)
Counseling on "increasing the hard skills of housewives as an effort to increase family income through training in making salted eggs in Bajo Village, Soromandi District" was carried out in August by involving various community groups including duck breeders, Soromandi Village officials, and the community around the service location. This activity was carried out through counseling and discussion as well as short training through demonstration and practice on salted egg making. This extension involved more than 37 participants from the planned 20 participants and also involved 3 students who were in their final semester. The results of the extension showed that the extension participants were very enthusiastic about this training meter can be seen from active participation in all activities, especially during discussion and practice sessions and increased understanding of salted egg making in an effort to increase the added value of duck eggs produced including to increase egg storage time so that it can be consumed in a relatively longer period of time than ordinary consumption eggs and increase the selling value of eggs. Keywords: Eggs, salted eggs, dedication, Bajo Village